How do we make sense of chaos? Navigating health research regulation through the liminality of the Brexit process. (June 2018) - Laurie, Graeme
This article examines the Brexit process through the anthropological lens of liminality. As a concept that explains the impact of change and transformation on human experience, it is argued that liminality is an especially valuable perspective to understand better the phenomenon of Brexit, particularly as to how this might impact on the regulation of human health research. A central feature of liminality is its attention to process; that is, the identification of milestone thresholds within a series of events involving change. More particularly, liminality has a degree of predictive power about certain influencing factors on transformational processes and their outcomes. In this regard, the pivotal role of law is subjected to close scrutiny in the period leading up to March 29, 2018: one year before the so-called Brexit Day. The European Union (EU) (Notification of Withdrawal) Act 2017 was the threshold trigger for the Brexit process, while the EU Withdrawal Bill 2017–2019 has as its objective the shepherding through of the United Kingdom in its departure from the EU. The argument is made that these events are liminal moments in European legal and human history; moreover, lessons from history are used to identify the specific implications for human health research as an area of human activity that will be profoundly impacted by the Brexit process. This analysis also provides a means to reflect on the broader implications of what a disruptive process such as Brexit means for law generally.